Perspektywa aksjologiczna w socjologii gospodarczej i ekonomicznej - Zdun, Magdalena (Annales. Etyka w Życiu Gospodarczym, 2020)
Axiological studies have been part of sociological research into business activity since the beginnings of the field. But there is still no agreement among scholars as two major concepts that are competing for dominance. One, building on the ideas proposed by Max Weber, advocates the priority of value over instrumental rationality, and it follows the path typical of ideological determinism. The other, with its roots in Karl Marx’s historical materialism, argues for the primacy of matter over mind. What these two have in common is the presence of two aspects, axiological and existential. The difference lies in their position of importance. Each approach makes different kinds of reductions, which are challenged by contemporary socio-economic systems that operate according to post-industrial logic. The goal of this article is to arrive at a new understanding of economic axiology. This understanding must be free from any reductionism that would assign the axiology radically different roles – either as a dependent or independent variable in growth. Economic axiology will be presented as a central category, a product of human interaction, and both a contributor to and an outcome of growth. Last but not least, based on the principle of double morphogenesis, specific economic axiologies will be identified.